Assessment of iron intake and the state of knowledge about its disturbances and food sources among students of Poznan universities - Siemienas, Natasza; Kanikowska, Alina; Kucharski, Marcin A.; Grzymisławski, Marian (Journal of Medical Science, 2014)
Introduction. Iron is one of many essential mineral components necessary for normal functioning of organisms. This microelement takes part in transport of oxygen from the lungs to the tissues, DNA synthesis, and is essential for normal activity of numerous enzymes. Aim. The aim of the work was the assessment of iron consumption among students of Poznan universities with consideration of the need for this mineral component. Material and methods. The study was conducted between the months of February and October 2012. Based on the randomly chosen study group, 100 people were analyzed – 66 females and 34 males. In total 25 people from each of the four Poznan universities: Poznan University of Medical Sciences, August Cieszkowski University of Life Sciences, Poznan University of Technology, as well as Eugeniusz Piasecki Academy of Physical Education were included into the studied population. In this study a questionnaire was a tool used in the analysis. Statistical analysis was conducted with the use of computer programs: STATISTICA version 10 and Microsoft Office Excel 2007. Determination of average values of iron, vitamin C, calcium and fiber intake, was performed with the use of DIETETYK 2011.Results. Satisfaction of the need for iron differs depending on the university and gender. The low iron intake was observed at Poznan University of Medical Sciences, while the high one at the University of Natural Science. Men (25) more often delivered with food adequate amount of iron in comparison to women (3). Increase in iron intake was observed together with the increase in the amount of calories in the diet as well as higher BMI. The study also showed that chronically ill people as well as women heavily bleeding during menses more frequently suffered from anemia. The main source of heme iron for the students was poultry meat, while the source of non-heme iron were mainly whole-wheat products.